2014
DOI: 10.1523/jneurosci.5044-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Being Imitated on Motor Responses Evoked by Pain Observation: Exerting Control Determines Action Tendencies When Perceiving Pain in Others

Abstract: Brain-imaging research has shown that experiencing pain oneself and perceiving pain in others lead to a similar pattern of activation, suggesting that the latter is based on internal simulation of the observed pain. Further evidence for this idea stems from transcranial magnetic stimulation measuring corticospinal excitability (CSE). It has been demonstrated that our motor cortex is involved whenever we observe another person receiving painful stimulation to the hand (Avenanti et al., 2005). However, both decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
10
2
Order By: Relevance
“…The current findings can be compared with those of a recent paper demonstrating that corticospinal excitability during the observation of painful stimuli applied to another's hand was increased when that hand imitated the participant's actions, compared with when it did not [56]. The authors suggested that being imitated by the hand gave the participant a sense of control over the hand and that this increased corticospinal excitability.…”
Section: (C) General Discussionsupporting
confidence: 51%
“…The current findings can be compared with those of a recent paper demonstrating that corticospinal excitability during the observation of painful stimuli applied to another's hand was increased when that hand imitated the participant's actions, compared with when it did not [56]. The authors suggested that being imitated by the hand gave the participant a sense of control over the hand and that this increased corticospinal excitability.…”
Section: (C) General Discussionsupporting
confidence: 51%
“…We found no significant difference between the painful and the pain-free lifting techniques at the group level but corticomotor excitability was modulated by the extent to which the participants perceived the actor's pain (see 3.2). This differs from previous studies which found a general reduction of corticomotor excitability in the contralateral muscle when participants observed others in pain (Avenanti et al, 2005;Avenanti et al, 2006;Minio-Paluello et al, 2006;Avenanti et al, 2009a;Minio-Paluello et al, 2009;Avenanti et al, 2010;De Coster et al, 2014;Mahayana et al, 2014). However, all previous studies examining pain perception in others used an exogenous "flesh and bone" pain stimulus (i.e.…”
Section: Corticomotor Excitabilitycontrasting
confidence: 83%
“…However, all previous studies examining pain perception in others used an exogenous "flesh and bone" pain stimulus (i.e. a video clip showing a needle deeply penetrating the right first dorsal interosseous while the hand is passive) (Avenanti et al, 2005;Avenanti et al, 2006;Minio-Paluello et al, 2006;Avenanti et al, 2009a;Minio-Paluello et al, 2009;Avenanti et al, 2010;De Coster et al, 2014;Mahayana et al, 2014). Also, in all of these previous studies the actor's hand did not produce any reaction to pain or withdrawal movement.…”
Section: Corticomotor Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, such synesthesia conditions can be construed as a condition of loosened bodily boundaries between self and other (Ward & Banissy, 2015). Third, illusions of ownership of other's hand were found to modulate excitability of primary motor cortex when observing that hand being painfully stimulated (Avenanti, Bueti, Galati, & Aglioti, 2005;Bucchioni et al 2016;De Coster, Andres, & Brass, 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%